Jalan Ideologi Dalam Negara Demokrasi - Rocky Gerung (Budapest International Research and Critics University, 2015)
This study is about the path of ideology in a democratic country. Ideology is a psychic tool. It is used to link the historical conditions of a period to their future origins. A kind of